HIF-1α mediates tumor-nerve interactions through the up-regulation of GM-CSF in pancreatic ductal adenocarcinoma. (1st July 2019) - Wang, Haotian; Jia, Rujiang; Zhao, Tiansuo; Li, Xin; Lang, Mingxiao; Lan, Chungen; Wang, Hongwei; Li, Zengxun; Zhou, Bodong; Wu, Liangliang; Sun, Yan; Wang, Xiuchao; et al.
Abstract: Perineural invasion (PNI) is a typical pathological feature of pancreatic ductal adenocarcinoma (PDAC). PNI is associated with poor prognosis of PDAC patients, however, the underlying molecular mechanisms in the development of PNI have not been fully revealed. In this study, we found that the expression of GM-CSF and HIF-1α were dramatically increased in PDAC cells. The overexpression of HIF-1α and GM-CSF closely correlated with increased occurrence of PNI and cancer-related pain and shortened overall survival in PDAC patients. GM-CSF expression in PDAC cells was mediated by HIF-1α through direct binding to the hypoxia response element in the GM-CSF promoter. The activated HIF-1α can up-regulate GM-CSF expression and secretion, which promoted the migration of Schwann cells in tumor microenvironment. Furthermore, GM-CSF overexpression could rescue the inhibition of Schwann cells migration by HIF-1α knockdown. Moreover, HIF-1α inhibition with PX478 drastically reduced the expression level of GM-CSF and decreased the PNI in a PDAC xenograft mouse model. Overall, our results demonstrated that the HIF-1α/GM-CSF pathway is involved in the tumor-nerve interactions and promotes the occurrence of PNI. The blockade of this signal might help to inhibit PDAC progression. Highlights: Up-regulated GM-CSF had intense relationship with perineural invasion in PDAC. HIF-1α transactivated GM-CSF gene expression, thus promoting Schwann cell migration. HIF-1α inhibition reduced GM-CSF levels and decreased the perineural invasion in PDAC.